Parts in Play: The Rosalynde Osborne Stearn Collection at McGill University - Flegel, Loretta (Université Concordia, 2003)
Keywords: Théâtre; Université McGill

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

Between the Future and the Present: Montreal University Student Youth and the Post-War Years, 1945-1960 - Hébert, Karine (Cultures of Citizenship in Post-War Canada, 1940-1955, 2003)
Keywords: Université McGill; Université de Montréal; Étudiants

Dans le mouvement étudiant à McGill - Lévesque, Andrée (Madeleine Parent, militante, 2003)
Keywords: Mouvement étudiant; Parent; Madeleine; Université McGill; Étudiants

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Number: 1
Keywords: McEachran; Duncan McNab; Université McGill; École de médecine vétérinaire

Self-Identification Processes and their Reflection in the Language of Fourth-Wave Emigrants in Montreal - Migdissova, Svetlana (Université McGill, 2003)
Keywords: Langue; Russes

Intersecting Discourses: Deaf Institutions and Communities in Montreal, 1850-1920 - Perreault, Stéphane- D (Université McGill, 2003)
Keywords: Clercs de Saint-Viateur; Communautés religieuses; Institution des sourdes-muettes; Institution des sourds-muets; Soeurs de la Providence; Sourds

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment—despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

'Justice in the Premises': Family Violence and the Law in Montreal, 1825-1850 - Pilarczyk, Ian C. (Université McGill, 2003)
Keywords: Criminalité; Droit; Enfants; Famille

Prendre et trouver sa place: discours hétéronormatifs et pratiques hétérosexuelles dans un cruising bar de Montréal - Lebrun, Aurélie (Université McGill, 2003)
Keywords: Alcool

Programmes intersectoriels pour les enfants exposés à la violence conjugale: recension des écrits et pistes d'actions pour la région de Montréal - Harper, Elizabeth (Université McGill, 2003)
Keywords: Enfants; Famille

Crisis? What Crisis?: Anglophone Musicmaking in Montreal - Stahl, Geoff (Université McGill, 2003)
Keywords: Anglophones; Musique

In the Shadow of the Mountain: A Historical Re-Evaluation of the 1988 Outremont Dispute - Herman, Dana (Université McGill, 2003)
Keywords: Juifs; Outremont

Hearing (Unheard) Voices: Aboriginal Experiences of Mental Health Policy in Montreal - Macdonald, Mary Ellen (Université McGill, 2003)
Keywords: Autochtones

Growing Up in Three Languages: Triliteracy Practices of Chinese Immigrant Children in Quebec - Curdt-Christiansen, Xiao Lan (Université McGill, 2003)
Keywords: Chinois; Langue